A novel circRNA, circNUP98, a potential biomarker, acted as an oncogene via the miR‐567/ PRDX3 axis in renal cell carcinoma. Issue 17 (30th July 2020) - Yu, Rui; Yao, Jie; Ren, Yu
Abstract: In recent years, plenty of studies found that circular RNAs (circRNAs) were essential players in the initiation and progression of various cancers including the renal cell carcinoma (RCC). However, the knowledge about the circRNAs in carcinogenesis is still limited. Dysregulated expression of circNUP98 in RCC tissues was identified by the circular RNA microarray. RT‐PCR was performed to measure the expression of circNUP98 in 78 pairs of RCC tissues and adjacent normal tissues. Survival analysis was conducted to explore the association between the expression of circNUP98 and the prognosis of RCC. The function and underlying mechanisms of circSMC3 in RCC cells were investigated by RNAi, CCK‐8, Western blotting, bioinformatic analysis, ChIP assay, circRIP assay and dual luciferase reporter assay. CircNUP98 was up‐regulated in both RCC tissues and cell lines, and high expression of circNUP98 was correlated with poor prognosis of RCC patients. Silencing of circSMC3 inhibited the proliferation and promoted the apoptosis in a caspase‐dependent manner in RCC cells. Mechanistically, we revealed that silencing of circ NUP98 inhibited RCC progression by down‐regulating of PRDX3 via up‐regulation of miR‐567. Furthermore, STAT3 was identified as an inducer of circ NUP98 in RCC cells. CircNUP98 acts as an oncogene by a novel STAT3/circ NUP98/miR‐567/PRDX3 axis, which may provide a potential biomarker and therapeutic target for the treatment of RCC.